Publication status of completed registered studies in paediatric appendicitis: a cross-sectional analysis - Breil, Thomas; Hoffmann, Georg F.; Ries, Markus (BMJ open, 2018)
Objective: Appendicitis is considered the most frequent surgical emergency in children. While the management of paediatric appendicitis is evolving, the precise amount of unpublished completed trials, potentially introducing bias into meta-analyses, is unknown. Controversial issues include the appropriate choice of surgical procedures, criteria for diagnosis of appendicitis, the role of antibiotic treatment and pain management. Selective reporting may introduce bias into evidence-based clinical decision-making, and the current, precise extent of unpublished results in paediatric appendicitis is unknown. We therefore assessed the publication status of completed clinical studies involving children registered on ClinicalTrials.gov. Design: Cross sectional analysis. STrengthening the Reporting of OBservational studies in Epidemiology criteria were applied for design and analysis. Setting and participants: ClinicalTrials.gov was queried for completed studies which were matched to publications on ClinicalTrials.gov, PubMed or Google Scholar. If no publication could be identified, principal investigators were contacted. Interventions/exposure: Observational analysis. Primary and secondary outcome measures: The proportion of published and unpublished studies was calculated. Subgroup analysis included studies on surgical procedures, diagnosis, antibiotic treatment and pain management. Results: Out of n=52 completed clinical studies involving children with appendicitis, n=33 (63%) were published and n=19 (37%) were unpublished. Eighty-three per cent (n=43/52) of clinical trials assessed the above-listed controversial issues. Diagnostic studies were most rigorously published (91% of trials reported), data on surgical procedures, antibiotic and pain management were less transparent. Sixty-six per cent of interventional studies and 60% of randomised studies were published. Median time-to-publication, for example, the delay between completion of the trial until public availability of the results was 24 (IQR 12-36), range 2-92 months. Conclusion: Despite the importance of appendicitis in clinical practice for the paediatric surgeon, there remains scientific uncertainty due to unpublished clinical trial results with room for improvement in the future. These data are helpful in framing the shifting paradigms in paediatric appendicitis because it adds transparency to the debate.